A new synonym of titanattus parvus (Mello-Leitão, 1945) (araneae: salticidae: thiodinini) - Rubio, Gonzalo Daniel (2021)
Most thiodinines are rare in collections, and this can lead to fragmented knowledge and some mistakes. In this brief contribution Titanattus acanjuba Bustamante & Ruiz is newly synonymized with T. parvus (Mello-Leitãão) and is illustrated by new photographs and drawings. Diagnostic characters for its recognition are provided.